IL‐5‐stimulated eosinophils adherent to periostin undergo stereotypic morphological changes and ADAM8‐dependent migration. Issue 10 (5th May 2017) - Johansson, M. W.; Khanna, M.; Bortnov, V.; Annis, D. S.; Nguyen, C. L.; Mosher, D. F.
Summary: Background: IL‐5 causes suspended eosinophils to polarize with filamentous (F)‐actin and granules at one pole and the nucleus in a specialized uropod, the "nucleopod, " which is capped with P‐selectin glycoprotein ligand‐1 (PSGL‐1). IL‐5 enhances eosinophil adhesion and migration on periostin, an extracellular matrix protein upregulated in asthma by type 2 immunity mediators. Objective: Determine how the polarized morphology evolves to foster migration of IL‐5‐stimulated eosinophils on a surface coated with periostin. Methods: Blood eosinophils adhering to adsorbed periostin were imaged at different time points by fluorescent microscopy, and migration of eosinophils on periostin was assayed. Results: After 10 minutes in the presence of IL‐5, adherent eosinophils were polarized with PSGL‐1 at the nucleopod tip and F‐actin distributed diffusely at the opposite end. After 30‐60 minutes, the nucleopod had dissipated such that PSGL‐1 was localized in a crescent or ring away from the cell periphery, and F‐actin was found in podosome‐like structures. The periostin layer, detected with monoclonal antibody Stiny‐1, shown here to recognize the FAS1 4 module, was cleared in wide areas around adherent eosinophils. Clearance was attenuated by metalloproteinase inhibitors or antibodies to disintegrin metalloproteinase 8 (ADAM8), a major eosinophil metalloproteinase previously implicated in asthma pathogenesis. ADAM8 was not found in podosome‐like structures, which are associated with proteolytic activity in other cell types. Instead, immunoblotting demonstrated proteoforms of ADAM8 that lack the cytoplasmic tail in the supernatant. Anti‐ADAM8 inhibited migration of IL‐5‐stimulated eosinophils on periostin. Conclusions and Clinical Relevance: Migrating IL‐5‐activated eosinophils on periostin exhibit loss of nucleopodal features and appearance of prominent podosomes along with clearance of the Stiny‐1 periostin epitope. Migration and epitope clearance are both attenuated by inhibitors of ADAM8. We propose, therefore, that eosinophils remodel and migrate on periostin‐rich extracellular matrix in the asthmatic airway in an ADAM8‐dependent manner, making ADAM8 a possible therapeutic target.